AQUAHEALTH: Physiochemical parameters and Vibrio spp. abundance in water samples gathered in the Adriatic Sea - Jurica Jug-Dujaković; Ana Gavrilović; Anamarija Kolda; Jakov Žunić; Kristina Pikelj; Eddy Listeš; Darija Vukić Lušić; Irena Vardić Smrzlić; Lorena Perić; Mansour El-Matbouli; Atle Lillehaug; Semir Lončarević; et al. (PANGAEA, 2022)
The genus Vibrio includes > 60 species that are autochthonous and ubiquitous aquatic microorganisms, members of the bacterial community in marine environments worldwide. Given their impact on human and animal health and the relative ease of their cultivation, Vibrio species have been well studied: the genus includes human and animal pathogens that have caused major diseases around the world (e.g. cholera or vibriosis). The dataset contains Vibrio spp. abundance and measurements of environmental parameters (temperature, salinity, total dissolved solids, pH, dissolved oxygen, total nitrogen, total phosphorus, total particulate matter, particulate organic matter and particulate inorganic matter), gathered at Mali Ston Bay in the Adriatic Sea. Water sampling was conducted at two locations: a floating cage fish farm (located near small island Maslinovac) and a control site (near island Pučenjak) at different depths (0.5 m, 5 m, 10 m and 18 m). The sampling period covers seasonal measurements between 2016 and 2019.